Sobre heroísmo e anti-heroísmo: a configuração da personagem protagonista em Aquilino Ribeiro e em Guimarães Rosa - Nascimento, Marília Angélica Braga do (2018)
The literary creation of the Portuguese writer Aquilino Ribeiro (1885-1963) and the work of the Brazilian writer Guimarães Rosa (1908-1967) offer more than enough material to a rapprochement of comparative nature. The present work sustains this effective possibility and proposes a reading that considers the fundamental role of the authors and their world perspective in the construction of their characters and the organicity of the work as a whole, presenting as main objective the critical and reflexive analysis of characters of both writers described above, in special those ones that features the narratives “A volta do marido pródigo” and “A hora e vez de Augusto Matraga”, reunited in Sagarana (1946), opening work of the Brazilian writer, and Mina de diamantes (1958), work of the Portuguese writer, which form the main corpus of this research. The reflection of the object of study takes as hypotheses a supposed inadequacy of the theoretical and critical stance that insists on designating, indistinctly, as “hero” the narrative protagonist, proceeding the hero concept in his relationship with the character, from the notions presented in treaties and manuals of theoretical nature and some critical texts, discussing them in order to delimit better the referred concept and observe implications concerning the focused characters. The resulting discussion also considers the concept of “antihero”, comprehending it as subversion to the traditional hero models and observing its deployments, as far as it resumes the characters of the Spanish rascal, the trickster and the Brazilian rascal, pointing out similar aspects between these characters and verifying confluences and discrepancies in relation to the protagonists of Aquilino and Rosa. The question raised in discussion was motivated, therefore, by the interest in considering the peculiar setups of Diamantino Dores, Lalino Salãthiel and Augusto Matraga, whose results point out, in relation to this last one, a relative closeness with traditional hero models, and a divergence of the other two concerning those models, since it drifts more to an antihero, taking us to determine the hypothesis previously introduced and disagree with the critical stance issue.